Influência do tratamento criogênico no desempenho de ferramentas de aço rápido - Silva, Flávio José da (1999)
The performance of cutting tools of high speed Steel tools ABNT M2 cryogenic treated is studied in this work. The cryogenic treatment consists of submitting the tools to temperatures of -196 °C using vapour of nitrogen. As a result there will be less residual austenite and precipitation of very fine carbides. Machining tests were carried out in laboratory and in the production line of an automotive industry. The treated tools gave better results than untreated tools for some machining tests. The life of treated tools had an increase of about 44 % in rapid facing tests. The treatment also increases tool life from 60 to 343 % when drilling ABNT 8640 Steel, mainly when the end life criterion used is catrastophic ruptura of the tool. No effect of cryogenic treatment in the tools performance was observed in face milling operations. Milling tests in the production line revealed that the treatment is detiimental to the life of TiN coated tools. It was also observed no effect when machining with center drills. Pin on disc wear tests and microstructure analysis were also carried out to support the results from the machining tests. The results shown that the cryogenic treatment do not change neither the percentage of residual austenite nor the tool hardness. The improvement of the wear resistance in some tests can be attributed to the precipitation fine carbides.